Trituration Proving of Australian Acacias (WA) - Moore, Sally (Homœopathic Links, 2019)
To date, a few Australian plants have been proven and used as homoeopathic remedies.We believe that the Australian native flora provides a yet untapped reservoir of healing potential.Four Australian Acacia species were used in the trituration: Acacias dentifera, pulchella, floribunda and longifolia.Potencies are available in the 3C, 4C and 5C range.
Keywords: Australian acacias (WA); C4 trituration; hay fever; liver issues; circulatory system; company; trauma; mass destruction; shock; play and time management